Espectroscopia de ultrassom como método alternativo para a determinação das características físico-químicas do leite de búfalas - Melo, Waldjânio de Oliveira; Monteiro, Bruno Moura; Chaves, Luciara Celi da Silva; Santos, Eduardo Riodades Daher; de Souza, Damazio Campos [UNESP]; de Amorim, Bianca Souza; de Faria Junior, Sebastião Pereira; Ribeiro Filho, José Dantas; Faturi, Cristian; Viana, Rinaldo Batista (FapUNIFESP (SciELO), 2018)
This study aimed to use ultrasound spectroscopy for the determination of the physical-chemical characteristics of buffalo milk and compare it to theinfrared method. Levels of fat, protein, lactose and non-fat solids (NFS) were determined in milk samples of 22 buffaloes (n = 383) with initial milk production of 6.97 ± 1.55 litres. The respective average results for the fat, protein, lactose and NFS of the individual samples were 6.31%, 3.81%, 4.99% and 9.75% for the infrared method-PO ANA 009 and 7.16%, 2.5%, 6.28% and 9.41% using ultrasound spectroscopy. There were significant differences (P<0.0001) in the levels of all of the components analysed between the two methods studied. Results obtained in the analyses using the ultrasonic milk analyser (Ekomilk Total®) were different from those obtained by the infrared method-PO ANA 009 (ESALQ), but they showed a high positive correlation for fat (r =0.84108, P<0.0001), moderate correlation for NFS(r= 0.71284 P = 0.0022), low correlation for lactose (r= 0.32197; P<0.0001) and the absence of correlation for protein(r= -0.00284, P<0.0001). Therefore, ultrasound spectroscopy can be used forthe determination of fat. For the other constituents of buffalo milk, in order to use the ultrasonic analyser, it is suggested that further studies should be conducted for technical and methodological adjustments.
Ultrasound spectroscopy as an alternative method to measure the physical-chemical constituents of buffalo milk
Keywords: Buffaloes; Fat; Infrared; Milk composition; Protein